Effectiveness of mobile SMS based counselling intervention in improving the knowledge, attitude, and practices of HIV/ AIDS patients enrolled in hospitals/NGOs in Terengganu, Malaysia: a mixed mode study protocol - Hossain, Md Mosharaf; Mat Min, Ruhani; Muhammad, Zikri; Mani, Kulanthayan K. C. (BioMed Central, 2020)
Background: HIV/AIDS is one of the most serious problems in many parts of the world, and is a high priority for health managers and decision-makers. The aim of the qualitative part of this study will be to develop a mobile SMS (short messaging services) counselling intervention to prevent HIV/AIDS, while the quantitative part will be to test the effectiveness of a mobile SMS counselling intervention to improve the knowledge, attitude, and practices of patients concerning the prevention of HIV/AIDS. Method: A mixed methods approach will be used. Qualitative part: Design: focus group discussions (FGDs) will be conducted. Setting: Hospital/NGOs in Terengganu, Malaysia. Participants: Three FGDs will be conducted with male and female HIV/AIDS patients, and one group of local community leaders. One FGD will be conducted for each group. Three in-depth interviews (IDIs) will be conducted with patients who had HIV/AIDS, of which one will be female. Quantitative part: Design: a cluster randomized clinical trial with 384 HIV/AIDS patients in Terengganu, Malaysia. Intervention: Mobile SMS counselling intervention for patients concerning the prevention of HIV/AIDS. Results: The main outcomes of this study will be the differences in knowledge, attitude, and practices of patients concerning the prevention of HIV/AIDS between the baseline and immediate follow-up after the intervention, and after 3 months. Conclusions: The mobile based SMS counselling intervention developed will be effective in improving the knowledge, attitude, and practices of patients concerning HIV/AIDS prevention in Terengganu, Malaysia.